2019
DOI: 10.1002/admt.201900150
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Skin‐Like Active Stretchable Electronics Based on Organic–Inorganic Composite Structures for Promotion of Cutaneous Wound Healing

Abstract: Recent studies on flexible/stretchable medical electronics are almost all focusing on passive monitoring of physiological signs for medical diagnostics, but rare reports have been found on those for active therapeutic purposes. Here, a novel infrared skin‐like active stretchable electronics (ISASE) is introduced with the organic–inorganic composite design for promotion of cutaneous wound healing, which can be conformally mounted anywhere on the human body due to its excellent flexibility and stretchability. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…The simple fabrication of elastic conductors via solution process is highly desirable for various applications, such as strain/pressure sensors, biosignal sensing electrodes, and signal transmission wires for stretchable electronics, to realize their functions in health monitoring, medical therapy, and soft robotics . For applications to human skin and humanoid robots, stretchability of over 55% and good mechanical durability for thousands of cycles of deformation are needed for long‐term stable operation .…”
mentioning
confidence: 99%
“…The simple fabrication of elastic conductors via solution process is highly desirable for various applications, such as strain/pressure sensors, biosignal sensing electrodes, and signal transmission wires for stretchable electronics, to realize their functions in health monitoring, medical therapy, and soft robotics . For applications to human skin and humanoid robots, stretchability of over 55% and good mechanical durability for thousands of cycles of deformation are needed for long‐term stable operation .…”
mentioning
confidence: 99%
“…Some studies have found that wound healing can be promoted by the near infrared light or low-level laser therapy, which is useful for promoting the fibroblast migration and reducing the inflammatory phase. [10][11] Studies have also found that the activity of Rac1 protein in fibroblasts plays a vital role in wound healing. Most experiments have proven that increasing the activity of Rac1 protein in fibroblasts can significantly promote wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Now, the corresponding endeavors have been shifted to the design and fabrication of near‐infrared (NIR) emitting OLED devices with peak emission wavelength (λ max ) ≥ 700 nm for its latent applications in night‐vision readable marking, telecommunication, noninvasive cutaneous wound healing, bioimaging, and photodynamic therapy. [ 3–7 ]…”
Section: Introductionmentioning
confidence: 99%